Implementing Interacty-Based Gamification Media to Improve Students’ Scientific Literacy in the Context of Local Culture - Ihfa Indira Nurnaifah Idris; Jumrah Jumrah; Abdul Razzaq; Sri Agustini; Dirgah Kaso Sanusi (Pustaka Digital Indonesia, 2026)
The urgency of this research lies in the need for innovative, interactive gamification-based learning media to enhance students’ scientific literacy, which remains relatively low, while simultaneously integrating local cultural contexts to support meaningful and relevant 21st-century learning. This study aims to examine the implementation of gamified learning using Interacty integrated with a local cultural context and its effect on students’ scientific literacy. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were eighth-grade students at a junior high school in Indonesia. Data were collected through scientific literacy tests, observation sheets, and student response questionnaires. Scientific literacy in this study refers to students’ ability to identify relevant information, represent problems in structured forms, apply problem-solving strategies, and interpret results within real-life contexts. The learning activities were designed using gamification elements such as interactive challenges and rewards through the Interacty platform, combined with culturally relevant contexts derived from local traditions and daily practices. The results showed a significant improvement in students’ scientific literacy, with the average score increasing from 63,5 in the pre-cycle to 74 in Cycle I and 80,3 in Cycle II. Students’ learning activities improved from a fair category (2,8) to a good category (3,5). In conclusion, the integration of gamification through Interacty and local cultural context effectively enhances students’ scientific literacy by creating a more engaging, meaningful, and contextual learning environment.